Obstacles to Online Yoga – Empirical Study on Yoogaia’s Passive Customers - Savelainen, Anna (My University, 2015)
Yoga is an ancient Indian physical and mental practice that has become extremely popular in the Western World, and is nowadays also available on Internet. The case firm of the study is a Finnish start-up company Yoogaia that offers yoga and other body and mind exercises online. Yoogaia’s special feature is that an online class can be attended with a web camera, which enables two-way interaction. Yoogaia has a large register of customers, but only a minority of them is currently paying for the service. The research purpose is thus to find out what are the obstacles for Yoogaia’s passive registered customers to buy the service. In order to answer the research problem three objectives were set: 1) to define the potential beneficial elements in this field of business: yoga service online, 2) to examine empirically what are regarded as Yoogaia’s beneficial elements, and 3) to empirically discover the reasons for customers’ passive behavior. As the study is quantitative by its nature a theoretical framework was created to serve as a basis for the empirical analysis. Yoga, online environment and membership were recognized as the beneficial elements in Yoogaia’s business idea. In addition four supplementary theme interviews were performed before creating the questionnaire. All in all 599 valid answers were received, of which 26 were from sign-ups who had not taken advantage of the free trial. The results were analyzed with IBM SPSS program using factor analysis and cluster analysis as methods. It appeared that Yoogaia’s main benefits were relaxation from yoga practice, price, flexibility, quick reactivity and communication provided by Yoogaia. The main reasons for having joined Yoogaia were free trial and special offers. That there no longer was a possibility to attend a singular class was considered as a disadvantage. Three segments were created according to their considerations about Yoogaia: True yogis, Happy customers and Busy yogis, and their potential for Yoogaia were estimated. Happy customers appeared to be the most potential ones. The only reason for passive behavior that came out was the fact that Yoogaia is not available via tablet. The identified obstacles for buying the service were: the assumption that signing up was done out of curiosity or because of the free trial, or reluctance to pay the full price for the service.
Keywords: yoga; online yoga; online environment; e-commerce; membership; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|